THE ROLE OF FINANCIAL INFORMATION SYSTEMS, INTERNAL AUDIT, AND INVESTIGATIVE AUDIT IN ENHANCING PUBLIC SECTOR FINANCIAL ACCOUNTABILITY: SYSTEMATIC LITERATURE REVIEW - Nurul Azizah Tamang; Arifuddin; Syarifuddin (ZILLZELL MEDIA PRIMA, 2026)
Public sector financial management demands transparency and accountability to realize good governance. However, challenges such as limited human resource competence, weak internal control, and fraud risks remain obstacles in the preparation of government financial statements. This study aims to review the role of financial information systems, internal audit, and investigative audit in enhancing public sector financial accountability. The method used is a Systematic Literature Review (SLR) by analyzing 20 articles published between 2021–2025, consisting of national and international literature selected through databases such as Scopus, Web of Science, EBSCO, Google Scholar, and Portal Garuda. The results show that financial information systems, particularly the implementation of SAKTI, serve as the technical foundation of transparency, but their effectiveness highly depends on user competence and organizational support. Internal audit, through the role of APIP/BPKP, functions as a preventive control mechanism that requires independence and institutional support. Meanwhile, investigative audit functions as a reactive protection instrument against fraud, in which the competence and experience of forensic auditors are dominant factors. The synthesis of the literature confirms that the synergy of these three aspects strengthens public financial accountability while supporting the implementation of good governance principles in state financial management.